Genetic polymorphisms in CYP4F2 may be associated with lung cancer risk among females and no-smoking Chinese population - Shi, Hongyang; Zhang, Yonghong; Wang, Yu; Fang, Ping; Liu, Yun (Frontiers in Oncology, 2023)
Background: Our study aimed to explore the potential association of the CYP4F2 gene polymorphisms with lung cancer (LC) risk. Methods: The five variants in CYP4F2 were genotyped using Agena MassARRAY from 507 cases and 505 controls. The genetic models and haplotypes based on logistic regression analysis were used to evaluate the potential association between CYP4F2 polymorphisms and LC susceptibility. Results: This study observed that rs12459936 was linked to an increased risk of LC in no-smoking participants (allele: OR = 1.38, p = 0.035; homozygote: OR = 2.00, p = 0.035; additive: OR = 1.40, p = 0.034) and females (allele: OR = 1.64, p = 0.002; homozygote: OR = 2.57, p = 0.006; heterozygous: OR = 2.56, p = 0.001; dominant: OR = 2.56, p < 0.002; additive: OR = 1.67, p = 0.002). Adversely, there was a significantly decreased LC risk for rs3093110 in no-smoking participants (heterozygous: OR = 0.56, p = 0.027; dominant: OR = 0.58, p = 0.035), rs3093193 (allele: OR = 0.66, p = 0.016; homozygote: OR = 0.33, p = 0.011; recessive: OR = 0.38, p = 0.021; additive: OR = 0.64, p = 0.014), rs3093144 (recessive: OR = 0.20, p = 0.045), and rs3093110 ((allele: OR = 0.54, p = 0.010; heterozygous: OR = 0.50, p = 0.014; dominant: OR = 0.49, p = 0.010; additive: OR = 0.54, p = 0.011) in females. Conclusions: The study demonstrated that CYP4F2 variants ws associated with LC susceptibility, with evidence suggesting that this connection may be affected by gender and smoking status.